Brain features of nearly drug‐naïve female monozygotic twins with first‐episode schizophrenia and the classification accuracy of brain feature patterns: A pilot study. Issue 2 (8th December 2020) - Zhang, Tao; Song, Jie; Chen, Ce; Li, Ran; Li, Yachen; Sun, Yun; Fang, Tao; Xu, Weiwei; Tian, Hongjun; Zhuo, Chuanjun
Abstract: Background: Data on differences in brain features between monozygotic (MZ) twins with and without schizophrenia are scarce. Methods: We compared brain features of female MZ twins with and without first‐episode schizophrenia and healthy controls ( n  = 20 each). Voxel‐based morphometry and tract‐based spatial statistics were used to analyze differences in brain structure. Whole‐brain effective connectivity (EC) and functional connectivity (FC) networks were constructed using resting‐state functional magnetic resonance imaging (rs‐fMRI) data. Results: Female twins with schizophrenia exhibited abnormal gray matter volume (GMV) in the basal ganglia and prefrontal and parietal cortices, impairments in the arcuate fasciculus, and significant disruptions (primarily decreases) in nine EC networks. They exhibited rs‐EC alterations involving the limbic areas and subcortex. Combined rs‐EC and rs‐FC data distinguished twins with first‐episode schizophrenia with high accuracy. Combined consideration of structural and functional features enabled the distinction of female MZ twins with schizophrenia from those without schizophrenia and healthy controls with 100% accuracy. Conclusions: Female MZ twins with schizophrenia exhibited increased GMV, white matter impairment, and disruptions in EC and FC networks. The combination of rs‐EC + rs‐FC data could distinguish female twins with schizophrenia from twins without schizophrenia and healthy controls with 97.4% accuracy, and the addition of structural brain features yielded a 100% accuracy rate. These findings may provide pivotal insight for further study of the mechanisms underlying schizophrenia. Abstract : Female monozygotic twins with schizophrenia exhibited decreased GMV in the prefrontal and parietal cortices, increased GMV in the basal ganglia, white matter (i.e., arcuate fasciculus) impairment, and disruptions in EC and FC networks. Female twins with schizophrenia exhibited significant disruptions (primarily decreases) in nine EC networks, most of which involved connections from limbic areas to the subcortex. The combination of rs‐EC and rs‐FC data could be used to distinguish female twins with schizophrenia from twins without schizophrenia and healthy controls with an accuracy of 97.4%, and the addition of structural brain features yielded an accuracy rate of 100%.